EFFECT OF SEEDS SOAKING AND VEGETATIVE PARTS NUTRITION WITH ACIDS OF ASCORBIC, CITRIC AND HUMIC ON MAIZE GROWTH - Kadhim, J. J.; Hamza, J. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
A field experiment was carried out during two spring seasons in 2019 and 2020. This study was aimed to increase dry matter weight and crop growth rate of maize. First factor in main plots was nutrition vegetative parts with ascorbic and citric (100 mg l-1) for both of them and humic (1 ml l-1), in addition to the control treatment (spraying of vegetative parts with distilled water only). Second factor in sub-plots was seeds soaking with same acids above, as well as the control treatment (soaking the seeds with distilled water only). Randomize complete block design in split plot arrangement was used with three replications. The results showed a significant superiority of seeds soaking in humic acid for traits of number of days from planting to 75% anthesis  and silking (66.4 and 66.3 day) and (72.3 and 72.3 day), plant height (194.0 and 230.8 cm), leaves area plant-1 (6969.5 and 6570.2 cm2), leaf area index (3.71 and 3.50), dry matter weight (11.6 and 12.2 ton ha-1), crop growth rate (3.0 and 3.2 g cm-2 day-1) and chlorophyll leaf content (60.2 and 69.5 SPAD) for both seasons, respectively. Effect of vegetative parts nutrition and interaction effect of both studied factors was non-significant for most traits. It can be concluded that seeds soaking in humic acid improved growth traits. It can be recommended to soak seeds of maize before planting in humic acid at concentration of 1 ml l-1.